THE EFFECT OF HUMAN RESOURCE MANAGEMENT ON THE QUALITY OF TEACHING IN SCHOOLS - Haslinda Mokodompit; Suhana Sarkawi (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This research examines the influence of human resource management (HRM) on the quality of teaching in schools. The main focus of the research is how the implementation of effective HRM can improve teachers' skills, knowledge and motivation to deliver quality teaching. Through selective recruitment processes, continuous training and structured performance evaluations, schools can ensure teachers have the competencies needed to optimise student learning outcomes. In addition, an appropriate reward and incentive system can encourage teachers to achieve their best performance. The research also highlights the importance of creating a positive and collaborative work environment where teachers can support each other and innovate in their teaching practices. The findings from this study suggest that strategic and holistic HRM is able to bring about significant improvements in the quality of teaching and, overall, improve the quality of education in schools.